Larval dispersal and connectivity of Ostrea edulis: A biophysical modelling review for restoration planning - Davide Carratù; Célia Laurent; Cosimo Solidoro; Donata Melaku Canu (Estuarine, Coastal and Shelf Science, 2026)

Physiological, morphological, and molecular adaptations of Pseudo-nitzschia multistriata to phosphorus limitation - Angela Pelusi; Luca Ambrosino; Sonia Dall’Ara; Martina Kralj; Federica Relitti; Tiziano Mattia Vollaro; Cosimo Solidoro; Maria Immacolata Ferrante; Federica Cerino (Harmful Algae, 2026)

The Geography of Mediterranean Benthic Communities Under Climate Change - Damiano Baldan; Yohann Chauvier‐Mendes; Diego Panzeri; Gianpiero Cossarini; Cosimo Solidoro; Vinko Bandelj (Global Change Biology, 2026)
Seafloors are crucial to marine ecosystems for the functions and services they provide. Benthic organisms, vital to these ecosystems, are particularly vulnerable to climate change. Rising temperatures, ocean acidification, and shifting currents disrupt benthic species and communities, yet future related impact assessments remain limited. Here, we trained species distribution models with predictors from state of the art physical and biogeochemical marine models and a large database of species records (> 100,000 occurrences) to project the current and future distributions of ~350 benthic species (excluding cephalopods, invasive species, and commercially exploited species) and their related changes per site in diversity (α‐) and community composition (β‐diversity) over the Mediterranean Sea. We predicted most species to shift their distribution northwards for all future scenarios due to changes in water temperature and dissolved oxygen close to the seafloor, with up to 60% of species experiencing range contraction, 77% moving northwards, 20% experiencing range fragmentation (measured as range disjunctions in models' output), and 30% moving toward deeper waters over time. Cold‐adapted species were more likely to face range contraction and shifts towards deeper waters, while warm‐adapted species were more likely to face range expansions and shifts towards shallower waters. α‐diversity increased in the Northern and decreased in the Southern Mediterranean, respectively. Changes in β‐diversity within sites highlighted compositional changes (species turnover) in communities located in the Aegean and Tyrrhenian Seas, in deep parts of the Ionian Sea, and in coastal regions of the Adriatic Sea. Climate‐smart, ecosystem‐based Marine Spatial Planning can capitalize on the identified hotspots of species losses, gains, stability, and turnover. Prioritizing connectivity in regions of strong turnover and extending protected areas in regions with stable α‐diversity and limited turnover is recommended for improved conservation actions.

Landscape‐Mediated Effects of Climate Change on Metacommunities Inhabiting Mediterranean Seagrass - Damiano Baldan; David Cunillera‐Montcusí; Marco Reale; Stefano Piani; Fabrizio Gianni; Serena Zunino; Gianpiero Cossarini; Stefano Salon; Cosimo Solidoro; Vinko Bandelj (Journal of Biogeography, 2025)
Aim Climate change affects dramatically biogenic habitats by altering the geographic distribution of the foundational species and the structure of landscapes they form. As a consequence, the associated biotic communities could experience habitat loss and fragmentation. In this paper, we assess how climate change impacts the geographic distribution of Mediterranean seagrass habitats and the cascading effects on the biodiversity of metacommunities they support. Location Mediterranean Sea. Taxon Posidonia oceanica and Cymodocea nodosa. Methods We employ state‐of‐the‐art physical and biogeochemical data for the Mediterranean Sea to model the seagrass distribution in the present climate using Species Distribution Models (SDMs). Based on the identified habitat configuration, we employ a neutral metacommunity model (NMM) to simulate virtual metacommunities structured by stochastic demographic processes and dispersal. Results SDMs were fitted with acceptable performances. We show a strong range contraction for both seagrass species (with uncertain predictions for the Southern and Eastern Mediterranean), a decrease in alpha diversity of associated communities, and an increase in beta diversity at the Mediterranean scale. Such changes are solely the result of the rearrangement of the landscape caused by climate change and create an offset for any distributional change related to niche effects. For different basins, we show that patterns of alpha diversity under realistic species dispersal are strongly correlated with habitat availability, while beta diversity is largely influenced by the changes in the spatial configuration of seagrass habitats. Main Conclusions By highlighting hotspots of metacommunity change linked to habitat fragmentation, our method can be useful for planning conservation and restoration measures at local and regional scales. We show that, besides niche effects, climate change can impact species distribution by altering the landscape structure.

The DANUBIUS-RI supersite of Po delta and North Adriatic Lagoons: a living lab on transitional environments in the Adriatic Sea - Francesca De Pascalis; Emilio Urbinati; Ali Aalifar; Leslie Aveytua Alcazar; Luca Arpaia; Marco Bajo; Andrea Barbanti; Francesco Barbariol; Mauro Bastianini; Debora Bellafiore; Federico Bellati; Alvise Benetazzo; et al. (Estuarine, Coastal and Shelf Science, 2025)

Performance of different modeling techniques in testing the impact of environmental variables on eel landing in Ichkeul Lake, a RAMSAR Wetland and UNESCO biosphere reserve - Sabrine Sahbani; Béchir Béjaoui; Ennio Ottaviani; Sihem Benabdallah; Eva Riccomagno; Enrico Prampolini; Donata Melaku Canu; Hechmi Missaoui; Cosimo Solidoro (Regional Studies in Marine Science, 2024)

Hypoxia extreme events in a changing climate: Machine learning methods and deterministic simulations for future scenarios development in the Venice Lagoon - Federica Zennaro; Elisa Furlan; Donata Canu; Leslie Aveytua Alcazar; Ginevra Rosati; Cosimo Solidoro; Andrea Critto (Marine Pollution Bulletin, 2024)

Ecophysiological responses of Fucus virsoides (Phaeophyceae, Fucales) to past and present nutrient conditions in the northern Adriatic - Emmanuelle Descourvières; Martina Mulas; Sara Natale; Raquel Sánchez de Pedro; Alessandro Alboresi; Cosimo Solidoro; Vinko Bandelj; Annalisa Falace (Marine Biology, 2024)
Fucus virsoides is a brown seaweed endemic to the Adriatic and the only species of its genus found in the Mediterranean. Historically widespread from the Venice lagoon (Italy) to Albania, this species has suffered a sharp decline and is currently threatened with extinction. Over the past three decades, the northern Adriatic has seen a shift towards oligotrophy conditions, yet the ecophysiology of F. virsoides in response to nutrients changes has been poorly studied. Addressing this gap is crucial for understanding the extent to which these environmental changes may have contributed to the species’ decline. To test our hypothesis that nutrient changes might be the primary driver of F. virsoides decline, we conducted a two-week experiment exposing germlings and adults to six different nutrient conditions. These included three Redfield ratios recorded in the Gulf of Trieste in 1996, 2007 and 2017, reflecting the shift from eutrophic to oligotrophic conditions experienced by F. virsoides in the wild. Additionally, the adults were exposed to three supplementary eutrophic conditions (naturally and artificially fertilized). Growth and physiological responses (measured via O 2 evolution and PAM fluorimetry) of F. virsoides to varying nutrient conditions were largely consistent, with only subtle effects observed. Our results highlight the species’ acclimatation potential, suggesting that short-term nutrient changes alone may not fully explain its decline. Understanding F. virsoides resilience to multiple environmental stressors is crucial for developing effective conservation strategies to preserve marine forests in the face of ongoing anthropogenic disturbances.

Mercury cycling in contaminated coastal environments: modeling the benthic-pelagic coupling and microbial resistance in the Venice Lagoon - Ginevra Rosati; Cosimo Solidoro; Célia Laurent; Leslie Aveytua Alcázar; Georg Umgiesser; Donata Canu (Water Research, 2024)

Toward the first documented extinction of a marine macroalga in the Mediterranean Sea? - Emmanuelle Descourvières; Vinko Bandelj; Adriano Sfriso; Martina Orlando-Bonaca; Vesna Mačić; Ljiljana Iveša; Silvija Kipson; Edi Gljušćić; Claudio Battelli; Isabella Moro; Cosimo Solidoro; Annalisa Falace (Regional Environmental Change, 2024)
Fucus virsoides is a glacial relict-species endemic to the Adriatic that was widespread from northern Italy to southern Albania. In recent decades, however, it has suffered an alarming decline. In this study, all available records were reviewed to reconstruct its historical and current occurrence and to investigate the possible causes of its decline. Comprehensive mapping revealed a continuing decline with a significant shift, leaving only about 20 fragmented populations. While the species is already classified as critically endangered in Albania, F. virsoides could be considered functionally extinct in Istria (Croatia), critically threatened with extinction in Italy and Montenegro and locally extinct in Slovenia. The status of the species in the rest of Croatia is still unclear. The remaining populations are located in areas characterised by low temperatures, low salinity and high nutrient concentrations. Long-term analyses of these key abiotic factors revealed profound changes that suggest a link to the species' decline. This study provides a thorough assessment of the overall status of F. virsoides and argues for its inclusion on the IUCN Red List. Immediate conservation measures are needed for the long-term survival of this species.

Identifying priority areas for spatial management of mixed fisheries using ensemble of multi‐species distribution models - Diego Panzeri; Tommaso Russo; Enrico Arneri; Roberto Carlucci; Gianpiero Cossarini; Igor Isajlović; Svjetlana Krstulović Šifner; Chiara Manfredi; Francesco Masnadi; Marco Reale; Giuseppe Scarcella; Cosimo Solidoro; et al. (Fish and Fisheries, 2024)
Spatial fisheries management is widely used to reduce overfishing, rebuild stocks, and protect biodiversity. However, the effectiveness and optimization of spatial measures depend on accurately identifying ecologically meaningful areas, which can be difficult in mixed fisheries. To apply a method generally to a range of target species, we developed an ensemble of species distribution models (e‐SDM) that combines general additive models, generalized linear mixed models, random forest, and gradient‐boosting machine methods in a training and testing protocol. The e‐SDM was used to integrate density indices from two scientific bottom trawl surveys with the geopositional data, relevant oceanographic variables from the three‐dimensional physical‐biogeochemical operational model, and fishing effort from the vessel monitoring system. The determined best distributions for juveniles and adults are used to determine hot spots of aggregation based on single or multiple target species. We applied e‐SDM to juvenile and adult stages of 10 marine demersal species representing 60% of the total demersal landings in the central areas of the Mediterranean Sea. Using the e‐SDM results, hot spots of aggregation and grounds potentially more selective were identified for each species and for the target species group of otter trawl and beam trawl fisheries. The results confirm the ecological appropriateness of existing fishery restriction areas and support the identification of locations for new spatial management measures.

The Mediterranean Forecasting System – Part 1: Evolution and performance - Giovanni Coppini; Emanuela Clementi; Gianpiero Cossarini; Stefano Salon; Gerasimos Korres; Michalis Ravdas; Rita Lecci; Jenny Pistoia; Anna Chiara Goglio; Massimiliano Drudi; Alessandro Grandi; Ali Aydogdu; et al. (Ocean Science, 2023)
The Mediterranean Forecasting System produces operational analyses and reanalyses and 10 d forecasts for many essential ocean variables (EOVs), from currents, temperature, salinity, and sea level to wind waves and pelagic biogeochemistry. The products are available at a horizontal resolution of 1/24∘ (approximately 4 km) and with 141 unevenly spaced vertical levels. The core of the Mediterranean Forecasting System is constituted by the physical (PHY), the biogeochemical (BIO), and the wave (WAV) components, consisting of both numerical models and data assimilation modules. The three components together constitute the so-called Mediterranean Monitoring and Forecasting Center (Med-MFC) of the Copernicus Marine Service. Daily 10 d forecasts and analyses are produced by the PHY, BIO, and WAV operational systems, while reanalyses are produced every ∼ 3 years for the past 30 years and are extended (yearly). The modelling systems, their coupling strategy, and their evolutions are illustrated in detail. For the first time, the quality of the products is documented in terms of skill metrics evaluated over a common 3-year period (2018–2020), giving the first complete assessment of uncertainties for all the Mediterranean environmental variable analyses.

Spatial patterns and drivers of benthic community structure on the northern Adriatic biogenic reefs - Fabrizio Gianni; Eva Turicchia; Marco Abbiati; Barbara Calcinai; Annalisa Caragnano; Saul Ciriaco; Federica Costantini; Sara Kaleb; Luigi Piazzi; Stefania Puce; Stefano Querin; Fabio Rindi; et al. (Biodiversity and Conservation, 2023)
The northern Adriatic Sea (NAS) hosts numerous biogenic subtidal reefs that are considered biodiversity hotspots. Several studies have already investigated the origin and biodiversity of these reefs. However, many of them are still unexplored and further knowledge is needed for their conservation. Here, the spatial variability, epibenthic community structure, and environmental features that characterize these habitats were investigated. Fifteen randomly selected reefs were sampled between 2013 and 2017, including some remote sites that have never been studied before. A fuzzy k-means clustering method and redundancy analysis were used to find similarities among sites in terms of epibenthic assemblages and to model relationships with abiotic variables. The results showed that these reefs are highly heterogeneous in terms of species composition and geomorphological features. The results were also consistent with previous studies and highlighted three main types of benthic assemblages defined by the dominance of different organisms, mainly reflecting the coastal-offshore gradient: nearshore reefs, generally dominated by stress-tolerant species; reefs at a middle distance from the coast, characterized by sponges, non-calcareous encrusting algae and ascidians; offshore reefs, dominated by reef builders. However, distance from the coast was not the only factor affecting species distribution, as other local factors and environmental characteristics also played a role. This kind of biogenic reefs in temperate seas are still poorly known. The present work contributed to shed further light on these habitats, by complementing the results of previous studies on their natural diversity, highlighting the specificity of the epibenthic communities of NAS reefs and the need to improve current, still inadequate, conservation measures.

Ocean acidification research in the Mediterranean Sea: Status, trends and next steps - Abed El Rahman Hassoun; Ashley Bantelman; Donata Canu; Steeve Comeau; Charles Galdies; Jean-Pierre Gattuso; Michele Giani; Michaël Grelaud; Iris Eline Hendriks; Valeria Ibello; Mohammed Idrissi; Evangelia Krasakopoulou; et al. (Frontiers in Marine Science, 2022)
Ocean acidification (OA) is a serious consequence of climate change with complex organism-to-ecosystem effects that have been observed through field observations but are mainly derived from experimental studies. Although OA trends and the resulting biological impacts are likely exacerbated in the semi-enclosed and highly populated Mediterranean Sea, some fundamental knowledge gaps still exist. These gaps are at tributed to both the uneven capacity for OA research that exists between Mediterranean countries, as well as to the subtle and long-term biological, physical and chemical interactions that define OA impacts. In this paper, we systematically analyzed the different aspects of OA research in the Mediterranean region based on two sources: the United Nation’s International Atomic Energy Agency’s (IAEA) Ocean Acidification International Coordination Center (OA-ICC) database, and an extensive survey. Our analysis shows that 1) there is an uneven geographic capacity in OA research, and illustrates that both the Algero-Provencal and Ionian sub-basins are currently the least studied Mediterranean areas, 2) the carbonate system is still poorly quantified in coastal zones, and long-term time-series are still sparse across the Mediterranean Sea, which is a challenge for studying its variability and assessing coastal OA trends, 3) the most studied groups of organisms are autotrophs (algae, phanerogams, phytoplankton), mollusks, and corals, while microbes, small mollusks (mainly pteropods), and sponges are among the least studied, 4) there is an overall paucity in socio-economic, paleontological, and modeling studies in the Mediterranean Sea, and 5) in spite of general resource availability and the agreement for improved and coordinated OA governance, there is a lack of consistent OA policies in the Mediterranean Sea. In addition to highlighting the current status, trends and gaps of OA research, this work also provides recommendations, based on both our literature assessment and a survey that targeted the Mediterranean OA scientific community. In light of the ongoing 2021-2030 United Nations Decade of Ocean Science for Sustainable Development, this work might provide a guideline to close gaps of knowledge in the Mediterranean OA research. Systematic Review Registration https://www.oceandecade.org/

Interactive effects of fishing effort reduction and climate change in a central Mediterranean fishing area: Insights from bio-economic indices derived from a dynamic food-web model - Davide Agnetta; Fabio Badalamenti; Francesco Colloca; Gianpiero Cossarini; Fabio Fiorentino; Germana Garofalo; Bernardo Patti; Carlo Pipitone; Tommaso Russo; Cosimo Solidoro; Simone Libralato (Frontiers in Marine Science, 2022)
Disentangling the effects of mixed fisheries and climate change across entire food-webs requires a description of ecosystems using tools that can quantify interactive effects as well as bio-economic aspects. A calibrated dynamic model for the Sicily Channel food web, made up of 72 functional groups and including 13 fleet segments, was developed. A temporal simulation until 2050 was conducted to evaluate the bio-economic interactive effects of the reduction of bottom trawling fishing effort by exploring different scenarios that combine fishery and climate change. Our results indicate that direct and indirect effects produce a net increase in biomass of many functional groups with immediate decline of trawlers’ catches and economic incomes, followed by a long term increase mainly due to biomass rebuilding of commercial species which lasts 5-10 years after fishing reduction. Synergistic and antagonistic effects caused by changes in the fishing effort and in climate characterize a specific functional group’s response in biomass which, in turn, modulate also the catch and income of the other fleets, and especially of those sharing target resources. However, trawler’s intra-fleet competition is higher than the others fleet effects. In the medium term, the effects of fishing effort reduction are higher than those of climate change and seem to make exploitation of marine resources more sustainable over time and fishery processes more efficient by improving ecosystem health.

Modeling Carbon Budgets and Acidification in the Mediterranean Sea Ecosystem Under Contemporary and Future Climate - Cosimo Solidoro; Gianpiero Cossarini; Paolo Lazzari; Giovanni Galli; Giorgio Bolzon; Samuel Somot; Stefano Salon (Frontiers in Marine Science, 2022)
We simulate and analyze the effects of a high CO 2 emission scenario on the Mediterranean Sea biogeochemical state at the end of the XXI century, with a focus on carbon cycling, budgets and fluxes, within and between the Mediterranean sub-basins, and on ocean acidification. As a result of the overall warming of surface water and exchanges at the boundaries, the model results project an increment in both the plankton primary production and the system total respiration. However, productivity increases less than respiration, so these changes yield to a decreament in the concentrations of total living carbon, chlorophyll, particulate organic carbon and oxygen in the epipelagic layer, and to an increment in the DIC pool all over the basin. In terms of mass budgets, the large increment in the dissolution of atmospheric CO 2 results in an increment of most carbon fluxes, including the horizontal exchanges between eastern and western sub-basins, in a reduction of the organic carbon component, and in an increament of the inorganic one. The eastern sub-basin accumulates more than 85% of the absorbed atmospheric CO 2 . A clear ocean acidification signal is observed all over the basin, quantitatively similar to those projected in most oceans, and well detectable also down to the mesopelagic and bathypelagic layers.

High-Resolution Reanalysis of the Mediterranean Sea Biogeochemistry (1999–2019) - Gianpiero Cossarini; Laura Feudale; Anna Teruzzi; Giorgio Bolzon; Gianluca Coidessa; Cosimo Solidoro; Valeria Di Biagio; Carolina Amadio; Paolo Lazzari; Alberto Brosich; Stefano Salon (Frontiers in Marine Science, 2021)
Ocean reanalyses integrate models and observations to provide a continuous and consistent reconstruction of the past physical and biogeochemical ocean states and variability. We present a reanalysis of the Mediterranean Sea biogeochemistry at a 1/24° resolution developed within the Copernicus Marine Environment Monitoring Service (CMEMS) framework. The reanalysis is based on the Biogeochemical Flux Model (BFM) coupled with a variational data assimilation scheme (3DVarBio) and forced by the Nucleus for European Modeling of the Ocean (NEMO)–OceanVar physical reanalysis and European Centre for medium-range weather forecasts (ECMWF) reanalysis ERA5 atmospheric fields. Covering the 1999–2019 period with daily means of 12 published and validated biogeochemical state variables, the reanalysis assimilates surface chlorophyll data and integrates EMODnet data as initial conditions, in addition to considering World Ocean Atlas data at the Atlantic boundary, CO 2 atmospheric observations, and yearly estimates of riverine nutrient inputs. With the use of multiple observation sources (remote, in situ , and BGC-Argo), the quality of the biogeochemical reanalysis is qualitatively and quantitatively assessed at three validation levels including the evaluation of 12 state variables and fluxes and several process-oriented metrics. The results indicate an overall good reanalysis skill in simulating basin-wide values and variability in the biogeochemical variables. The uncertainty in reproducing observations at the mesoscale and weekly temporal scale is satisfactory for chlorophyll, nutrient, oxygen, and carbonate system variables in the epipelagic layers, whereas the uncertainty increases for a few variables (i.e., oxygen and ammonium) in the mesopelagic layers. The vertical dynamics of phytoplankton and nitrate are positively evaluated with specific metrics using BGC-Argo data. As a consequence of the continuous increases in temperature and salinity documented in the Mediterranean Sea over the last 20 years and atmospheric CO 2 invasion, we observe basin-wide biogeochemical signals indicating surface deoxygenation, increases in alkalinity, and dissolved inorganic carbon concentrations, and decreases in pH at the surface. The new, high-resolution reanalysis, open and freely available from the Copernicus Marine Service, allows users from different communities to investigate the spatial and temporal variability in 12 biogeochemical variables and fluxes at different scales (from the mesoscale to the basin-wide scale and from daily to multiyear scales) and the interaction between physical and biogeochemical processes shaping Mediterranean marine ecosystem functioning.

Impact of Ocean Acidification on Ecosystem Functioning and Services in Habitat-Forming Species and Marine Ecosystems - Serena Zunino; Simone Libralato; Donata Melaku Canu; Giulia Prato; Cosimo Solidoro (Ecosystems, 2021)
Ocean acidification (OA) is expected to impact habitat-forming species (HFS), with cascading effects on the whole marine ecosystem and related services that are seldom quantified. Here, the changes in HFSs biomass due to OA are modeled using a food web ecosystem model, and the trophic and non-trophic cascading effects on the marine community are investigated. The food web model represents a well-studied coastal marine protected area in the NW Mediterranean Sea where coralligenous reefs and Posidonia oceanica meadows constitute important HFS. The model is used to implement 5 scenarios of habitat degradation, that is, reduction of HFS biomass, induced by increasing OA and to quantify the potential changes in ecosystem properties and indicators of ecosystem services over the next 100 years. The changes in ecosystem indicators highlight a decrease in the size of the system and a reorganization of energy flows suggesting a high degree of ecosystem development. All the proxies for ecosystem services show significant decreases in their values. Although representing only a portion of the possible impacts of OA, the findings are consistent with the idea that ecological systems can react to OA effects to maintain the level of ecosystem development, but the new organization might not be optimal from an anthropocentric viewpoint.

Nephrops norvegicus in the Adriatic Sea: Connectivity modeling, essential fish habitats, and management area network - Donata Melaku Canu; Célia Laurent; Elisabetta B. Morello; Stefano Querin; Giuseppe Scarcella; Nedo Vrgoc; Carlo Froglia; Silvia Angelini; Cosimo Solidoro (Fisheries Oceanography, 2021)
Knowledge of connectivity among subpopulations is fundamental in the identification of the appropriate geographical scales for stock status evaluation and management, the identification of areas with greater retention rates, and space‐based fisheries management. Here, an integration of hydrodynamic, biological, and habitat models results is used to assess connectivity and support the definition of essential fish habitats (EFH) in the Adriatic Sea, with reference to Nephrops norvegicus , an important benthic commercial resource, the recruitment of which is strongly related to larval dispersal from spawning to recruitment areas. We explored oceanographic and biological connectivity in the Adriatic Sea under a wide and representative variety of oceanographic conditions (winters 2006–2012) by tracking 3D trajectories of larvae released from different areas. We used a Lagrangian model that features a specific larval behavior module with explicit dependence on environmental parameters (i.e., temperature and sediment type) and that is driven by high‐resolution hydrodynamic and meteorological data. The results were used to partition the area in which Nephrops was observed into 20 homogenous management subareas; to assess the connection between spawning, recruitment, and harvesting grounds; and to identify potential subpopulation boundaries as well as the connectivity among the potential subpopulations. The results suggest the presence of at least three distinct subpopulations, which need to be independently managed and conserved, and confirms that the Jabuka‐Pomo pit is the most important spawning area, but alone it cannot sustain Nephrops populations throughout the Adriatic Sea. The results also show the importance to move from particle‐tracking to approaches based on integrated models.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

Past and Future Grand Challenges in Marine Ecosystem Ecology - Angel Borja; Jesper H. Andersen; Christos D. Arvanitidis; Alberto Basset; Lene Buhl-Mortensen; Susana Carvalho; Katherine A. Dafforn; Michelle J. Devlin; Elva G. Escobar-Briones; Christian Grenz; Tilmann Harder; Stelios Katsanevakis; et al. (Frontiers in Marine Science, 2020)

Novel metrics based on Biogeochemical Argo data to improve the model uncertainty evaluation of the CMEMS Mediterranean marine ecosystem forecasts - Stefano Salon; Gianpiero Cossarini; Giorgio Bolzon; Laura Feudale; Paolo Lazzari; Anna Teruzzi; Cosimo Solidoro; Alessandro Crise (Ocean Science, 2019)
The quality of the upgraded version of the Copernicus Marine Environment Monitoring Service (CMEMS) biogeochemical operational system of the Mediterranean Sea (MedBFM) is assessed in terms of consistency and forecast skill, following a mixed validation protocol that exploits different reference data from satellite, oceanographic databases, Biogeochemical Argo floats, and literature. We show that the quality of the MedBFM system has been improved in the previous 10 years. We demonstrate that a set of metrics based on the GODAE (Global Ocean Data Assimilation Experiment) paradigm can be efficiently applied to validate an operational model system for biogeochemical and ecosystem forecasts. The accuracy of the CMEMS biogeochemical products for the Mediterranean Sea can be achieved from basin-wide and seasonal scales to mesoscale and weekly scales, and its level depends on the specific variable and the availability of reference data, the latter being an important prerequisite to build robust statistics. In particular, the use of the Biogeochemical Argo floats data proved to significantly enhance the validation framework of operational biogeochemical models. New skill metrics, aimed to assess key biogeochemical processes and dynamics (e.g. deep chlorophyll maximum depth, nitracline depth), can be easily implemented to routinely monitor the quality of the products and highlight possible anomalies through the comparison of near-real-time (NRT) forecasts skill with pre-operationally defined seasonal benchmarks. Feedbacks to the observing autonomous systems in terms of quality control and deployment strategy are also discussed.

Editorial: Challenges and Opportunities for the EU Common Fisheries Policy Application in the Mediterranean and Black Sea - Simone Libralato; Franceso Colloca; Ali C. Gücü; Christos D. Maravelias; Cosimo Solidoro; Sebastián Villasante; Massimiliano Cardinale (Frontiers in Marine Science, 2018)

ATP Supply May Contribute to Light-Enhanced Calcification in Corals More Than Abiotic Mechanisms - Giovanni Galli; Cosimo Solidoro (Frontiers in Marine Science, 2018)

Modelling Marine Sediment Biogeochemistry: Current Knowledge Gaps, Challenges, and Some Methodological Advice for Advancement - Gennadi Lessin; Yuri Artioli; Elin Almroth-Rosell; Jerry C. Blackford; Andrew W. Dale; Ronnie N. Glud; Jack J. Middelburg; Roberto Pastres; Ana M. Queirós; Christophe Rabouille; Pierre Regnier; Karline Soetaert; et al. (Frontiers in Marine Science, 2018)

Corrigendum: Analysis of Long-Term Changes in a Mediterranean Marine Ecosystem Based on Fishery Landings - Tomaso Fortibuoni; Otello Giovanardi; Fabio Pranovi; Saša Raicevich; Cosimo Solidoro; Simone Libralato (Frontiers in Marine Science, 2017)

Marine Heat Waves Hazard 3D Maps and the Risk for Low Motility Organisms in a Warming Mediterranean Sea - Giovanni Galli; Cosimo Solidoro; Tomas Lovato (Frontiers in Marine Science, 2017)

Analysis of Long-Term Changes in a Mediterranean Marine Ecosystem Based on Fishery Landings - Tomaso Fortibuoni; Otello Giovanardi; Fabio Pranovi; Saša Raicevich; Cosimo Solidoro; Simone Libralato (Frontiers in Marine Science, 2017)

An ensemble of models for identifying climate change scenarios in the Gulf of Gabes, Tunisia - Lara Lamon; Jonathan Rizzi; Antonio Bonaduce; Clotilde Dubois; Paolo Lazzari; Leila Ghenim; Slim Gana; Samuel Somot; Laurent Li; Donata Melaku Canu; Cosimo Solidoro; Nadia Pinardi; et al. (Regional Environmental Change, 2014)

Recent Trends Towards Oligotrophication of the Northern Adriatic: Evidence from Chlorophyll a Time Series - Patricija Mozetič; Cosimo Solidoro; Gianpiero Cossarini; Giorgio Socal; Robert Precali; Janja Francé; Franco Bianchi; Cinzia De Vittor; Nenad Smodlaka; Serena Fonda Umani (Estuaries and Coasts, 2010)

Hydrological and biogeochemical features of the Northern Adriatic Sea in the period 2003–2006 - Giorgio Socal; Francesco Acri; Mauro Bastianini; Fabrizio Bernardi Aubry; Franco Bianchi; Daniele Cassin; Joan Coppola; Amelia De Lazzari; Vinko Bandelj; Gianpiero Cossarini; Cosimo Solidoro (Marine Ecology, 2008)
This paper reports on the main biogeochemical properties of the Northern Adriatic Sea in the period May 2003–November 2006 within the framework of the European program INTERREG III Italy‐Slovenia. Spatial and temporal distributions of water density, dissolved oxygen, nutrients (nitrogen, phosphorous and silicon) and chlorophyll a are presented. Multivariate methods such as fuzzy k‐means, self‐organising maps and cluster analysis were used to identify the different water masses and to characterise the temporal and spatial variability of the main biogeochemical features present in the area. The results confirm that the Po River outflows and the meteorological forcing factors are the main components triggering the alternation of stratification and mixing of the water column and that strongly affect the trophic state of the basin. In general, oligotrophic conditions dominate, and were more pronounced offshore, but mesotrophy occurred episodically in May 2004 and July 2005, when phytoplankton blooms were observed concomitant with vertical stability of the water column. A marked interannual variability was also observed, supporting the importance of maintaining long‐term observations of the basin.